Unraveling the origin of the "Turn-On" effect of Al-MIL-53-NO2 during H2S detection. Issue 2 (5th December 2019) - Zhu, Zan; He, Xiang; Wang, Wei-Ning
Abstract : Real fluorophores were found in nitro-functionalized metal–organic frameworks for H2 S detection using a representative MOF, Al-MIL-53-NO2 . Abstract : Nitro-functionalized metal–organic frameworks (MOFs), such as Al-MIL-53-NO2, have been widely used in quantitative hydrogen sulfide (H2 S) detection based on the "turn-on" effect, where fluorescence enhancements were observed upon contact with H2 S. This was believed to be caused by the fact that the electron-withdrawing –NO2 groups in the initial non-luminescent MOFs were reduced to electron-donating –NH2 groups in the sensing process. However, since most H2 S detection is conducted in a suspension system consisting of MOFs and solvents, it is still unclear whether these –NH2 groups are on MOFs or in the liquid. Using Al-MIL-53-NO2 as a model MOF, this work aims to answer this question. Specifically, the supernatant and undissolved particles separated from the Al-MIL-53-NO2 suspensions after being exposed to H2 S were analyzed systematically. The results showed that it is the free BDC-NH2 (2-aminobenzene-1, 4-dicarboxylic acid) in the solution rather than the formation of Al-MIL-53-NH2 that really caused the fluorescence enhancement. In particular, the formed BDC-NH2 was reduced from the shedded BDC-NO2 (2-nitrobenzene-1, 4-dicarboxylic acid) during the decomposition of Al-MIL-53-NO2, which was attacked by OH − in the NaHS solution. We anticipate that this work will offer new ways of tracing fluorophores for MOF-based sensing applications in aqueous systems.